2018
DOI: 10.1002/jsfa.8822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of medium‐chain triacylglycerols on Maillard reaction in bread baking

Abstract: These results led us to conclude that the fatty acid composition of the added lipids also influences properties that determine the tastiness of bread. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This study, thus, demonstrated that the glucose-lysine Maillard reaction is induced by light irradiation and yet inhibited by the presence of MCTs. Taken together with previous study results (Toyosaki, 2018) the inhibitory effect of MCTs on light irradiation induced glucose-lysine Maillard reaction is, hereby, proposed.…”
Section: Influence Of Mcts On the Induction Of Maillard Reaction By Lsupporting
confidence: 87%
See 1 more Smart Citation
“…This study, thus, demonstrated that the glucose-lysine Maillard reaction is induced by light irradiation and yet inhibited by the presence of MCTs. Taken together with previous study results (Toyosaki, 2018) the inhibitory effect of MCTs on light irradiation induced glucose-lysine Maillard reaction is, hereby, proposed.…”
Section: Influence Of Mcts On the Induction Of Maillard Reaction By Lsupporting
confidence: 87%
“…Building on previous work done and confirmation that MCTs inhibit the induction of the Maillard reaction during bread baking (Toyosaki, 2018), the relationship between the constituent fatty acids of the MCTs and Maillard reaction using a variety of fatty acids was investigated *Corresponding author. E-mail: toyosaki@koran.ac.jp.…”
Section: Introductionmentioning
confidence: 99%
“…Other important sources of dicarbonyls are the reactions of lipid and fatty acid peroxidation [32], metabolism of serine [33] and non-enzymatic conversion of glyceraldehyde-3-phosphate and dihydroxyacetone phosphate into MGO [34]. Due to the existence of multiple pathways of advanced glycation (Figure 1), AGEs demonstrate a high degree of heterogeneity and are represented with a variety of aliphatic, aromatic and heterocyclic structures, many of which have a cross-linking nature (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…We have found interesting knowledge that the fermentation of the dough is enhanced as a result of tracking from a few years ago on the food function properties of MCT's bread and also clarified the fact that MCT suppresses the induction of Maillard reaction (Toyosaki, 2018). Based on such research results, MCT believes that new knowledge can be brought up on the food function characteristics of bread.…”
Section: Introductionmentioning
confidence: 75%